Myocardial efficiency in severe asymptomatic primary mitral regurgitation: relation to quantitative measures of regurgitation. (14th October 2021) - Sorensen, J; Bergsten, J; Baron, T; Orndahl, L H; Kero, T; Bjerner, T; Hedin, E; Harms, H J; Flacshkampf, F A
Abstract: Objectives: To study the association of myocardial external efficiency (MEE) in mitral regurgitation (MR) towards routinely used quantitative indicators of disease severity and progression. Background: Quantitative assessment of LV function and regurgitation in asymptomatic severe primary MR is crucial for management. MEE is a load-independent indicator of mechano-energetic coupling and can be measured non-invasively using 11C-acetate positron emission tomography (PET). The role of MEE in this setting has not been studied. Methods: 48 asymptomatic patients with severe primary mitral regurgitation underwent PET, echo, and CMR on the same day. MEE was automatically derived from PET as the ratio of cardiac work (cardiac output * mean arterial pressure) and total left ventricular (LV) oxygen consumption (mean MVO2 * LV mass). LV function and mitral regurgitant volumes (RegVol) were measured by echo and CMR. MEE in MR was compared to healthy volunteers (n=9). MEE and parameters of regurgitation severity and of LV volumes and function were studied as predictors of outcome (valve surgery or death). Results: MEE was reduced in MR (21.5±4.2%) vs healthy volunteers (32.0±5.6%, p<0.001) and showed weak but significant correlations (r2<0.25) with regurgitation severity and LV volumes. There were 23 cardiac events (valve surgery: 22; cardiovascular death: 1) during follow-up (median 2.7 years, IQR 1.9–3.2). Univariate Cox models showed that MEE, echocardiographic left atrial volume as well as RegVol and LV ventricular volumes from both echo and CMR were significant outcome predictors (all p<0.05), while LVEF and NT-pro-BNP were not (p>0.05). Prediction by MEE was not affected by age, sex or BMI. When categorically divided by the median MEE was a strong predictor in Kaplan-Meier analysis (log-rank p=0.0004, figure 1) and remained independently significant, compared to all other univariate predictors in bivariate Cox models. Conclusions: This study suggests an important role of energetic insufficiency in progression of asymptomatic severe primary MR. Reduced MEE was linked to outcome independently of standard functional measures of regurgitation severity or left ventricular size and function. Strategies for improvement of myocardial energetics in MR are warranted. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish Heart-Lung Foundation